Physico-Chemical Properties and Bioactivity of Resinous Araucaria cunninghamii extract - Aishah Agustian; Ganis Lukmandaru; Rizki Arisandi (Masyarakat Peneliti Kayu Indonesia, 2025)
Resin has been identified as a promising non-timber forest product with the potential to generate high economic value. Araucaria cunninghamii is recognized as one of the most prominent sources of resin in Indonesia. This study aimed to evaluate the potential of resin from A. cunninghamii, focusing on its extractive properties. A total of 20 g of resin was extracted by separation and successive extraction methods using n-hexane, ethyl acetate, and methanol solvents. Subsequently, the n hexane extract was fractionated into neutral and acidic fractions. Subsequently, the acidic fraction underwent a saponification process, resulting in the isolation of an unsaponifiable fraction and a phenolic fraction. The components of analysis were identified through the utilization of a GC-MS analysis. The physicochemical test of the resin was conducted in accordance with the Indonesian National Standard (SNI 7636:2020), while the quantification of the total phenolic content was performed through the implementation of the Folin-Ciolceteu method. Furthermore, the measurement of antioxidant activity was conducted through 1,1-diphenyl-2-picryl-hydrazyl (DPPH) test (inhibition percentage). The results showed that the ethyl acetate extract exhibited the highest solubility. Araucaria cunninghamii contained a more dominant neutral fraction. Moreover, the highest level of total phenolic content was obtained in the n-hexane soluble fraction (6.84 mg GAE/g). A GC-MS analysis revealed the presence of oxygenated sesquiterpenes (31.5%), sesquiterpenes hydrocarbons (23.8%), and oxygenated diterpenes (19.9%) within the sample. Furthermore, the physicochemical tests exhibited ash content, acid number, and toluene insoluble content of 0.02%, 83.90 and 0.5%, respectively. Araucaria cunninghamii had relatively low antioxidant activity. In the phenolic fraction, antioxidant activity increased after partitioning of the n-hexane solubles. The phenolic fraction exhibited an increase in its inhibitory effect, with an increase from 19.5% to 28.8%. Further studies are necessary to detect phenolic and non-phenolic components affected by the intensity of antioxidant activity.